Strategi Digital Marketing Dalam Memperkuat Brand Image Pada Roti Kacang Mpok Atik Tebing Tinggi - Purba, Rakhmawati; Siahaan, Rumiris; Batubara, Rizki Wulanita; Ketaren, Abednego; Lubis, Abdillah Fenorian; Sepvira, Bulan; Faransiska, Faransiska; Saragih, Naumi Salsabillah; Siregar, Satya Pranaja; Victor, Victor; Kadariah, Siti (STIE Bina Karya, 2025)
MSMEs play a vital role in the country's economic growth by significantly contributing to job creation, poverty alleviation, and economic equality. Peanut bread is one of the typical souvenirs from the city of Tebing Tinggi besides lemang and other products. Currently, the development of peanut bread production businesses is increasingly widespread in Tebing Tinggi with various brands and flavors. One of them is the Mpok Atik peanut bread brand. One of the problems faced by this MSME is limited capital, where there is competition from large producers, and market access is still limited. This campus collaborative activity program is a type of community service activity in helping solve problems that exist in the community / MSMEs. The enlightenment provided by the team about digitalization plays a vital role in driving the growth of the Mpok Atik peanut bread MSME. By implementing various digital-based marketing, MSMEs can compete in the increasingly competitive modern era by utilizing technology to increase market access, improve brand image, and remain competitive. This peanut bread MSME excels because its products have the characteristics of a local identity, authentic taste.